PELAKSANAAN KINERJA HUMAS DAN PROTOKOL DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN KLATEN - , YOHANA POUTRIE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Local Government Performance can be seen from the performance of employees or government officials, the authors of this study focused on Klaten DPRD Secretariat. In assessing a person's job performance, performance evaluation is very important for all employees to measure employee performance and how to measure the extent to which the principal functions and duties of Public Relations and Protocol Klaten DPRD can be accomplished. The purpose of this study was to determine how the implementation of the performance of employees in the Public Relations and Protocol Klaten DPRD. This research was conducted using the method in Quantitative Approach (empirical), the research used data in accordance with the reality on the ground. In this study the target respondent was an employee at the Council of Public Relations and Protocol. The researchers used techniques in data collection are interviews, observation and documentation studies. From the research, employee performance and protocols of public relations section, the data shows that there are deviations of performance on the part of public relations and protocol Klaten regency. That is because there are many employees who commit acts of discipline and lack of personnel in the public relations and protocol, as well as the leadership that is not firmly against the clerks.